The Influence of Human Development Index on The Income Distribution Inequality In Yogyakarta - Rachmawatie, Dessy; Prakoso, Alim Yusuf (Jambura Agribusiness Journal, 2023)
The purpose of this study is to analyze whether the Human Development Index is a key factor in encouraging the income distribution inequality in DIY Province. The method used in this research is to use Fixed Effect Model, using Chow test and Hausman test. The type of data used in the form of secondary data which is research data, which is a combination of time series data from 2010-2020 and cross section data from 5 regencies in DIY Province. The data in this study are quantitative in nature, namely data obtained from the Central Bureau of Statistics in the form of numbers, including: Gini Index, HDI, GRDP, and LGI. The results showed that based on the results of the R-Square of 0.5424 which means the income distribution inequality in 5 regencies/cities in DIY Province has a change of 54.24% which is influenced by the HDI, GRDP, and LGI variables. While the value of 45.76% is influenced by variables outside the study. Based on the partial test, it was found that the HDI and LGI have a positive and significant effect on the income distribution inequality, while GRDP has no significant effect on income distribution inequality in 5 regencies/cities in DIY Province.